Significance of Biomarkers of Endothelial Dysfunction in Central Retinal Vein Occlusion - K. I. Belskaya; L. K. Moshetova; S. P. Kazakov (Oftalʹmologiâ)
Retinal vein occlusion is a severe vascular pathology of the retina, leading to a significant decrease in vision and blindness. Fundus lesion manifests itself as cystic edema of the macular region, long-lasting persistent macular edema is a poor prognostic sign.The purpose: to analyze the relationship between the clinical course of retinal vascular occlusion and the content of VEGF and MCP-1 in lacrimal fluid. The content of MCP-1 lacrimal fluid and VEGF lacrimal fluid was studied in 3 groups — in group I (patients with the central retinal vein occlusion, in group II (patients with the central retinal artery occlusion), in the control group (practically healthy individuals). The clinical course data are presented by data on best corrected visual acuity (BCVA) in patients of groups I and II and data on retinal thickness in fovea centralis (according to the results of OCT fovea centralis) in patients of group I. Statistical analysis showed no correlation between the studied biomarkers. The results showed a significant correlation of BCVA with retinal thickness in fovea centralis and a significant correlation with lacrimal fluid VEGF in group I patients, as well as a moderate correlation between lacrimal fluid VEGF and retinal thickness in fovea centralis.